The Phenomenon Of Pregnant Women's Anxiety In Facing Labor - Lutfiana Puspita Sari; Dewi Susilowati; Sofia Sagita (Poltekkes Kemenkes Surakarta, 2022)
Background: The delivery process is a natural event of conception in the form of a baby and placenta from the uterus that can cause anxiety. If anxiety in pregnant women is not managed properly, it will have an impact on the physical and psychological health of the mother and baby. Methods: This study uses descriptive methods. The implementation of the research will take place in December 2021–May 2022 at PMB Lutfiana. A total of 40 maternity mothers during phase I was active were obtained through a total sampling technique. The data collection technique uses the STAI scale. Data analysis using descriptive analysis. Result: The age characteristics of respondents aged 20–35 years included as many as 34 respondents (85%). The majority of low-educated elementary-junior high school students amounted to 21 respondents (52.5 %). The majority of respondents did not work, a total of 27 respondents (67.5%), and the majority of multiparous respondents amounted to 31 respondents (77.5%). The majority of maternity mothers' anxiety during the active phase was severe anxiety level, with 28 respondents (70%). The average anxiety score was 46.43, with 95% of the CI being at a score of 43.01-49.84. Conclusion: The majority of anxiety levels in active phase maternity mothers are severe anxiety levels.